The Concept of Christology: Exploring the Theological Understanding of the Divinity and Humanity of Christ (London Journal of Research In Humanities and Social Sciences, 2025)
Throughout the history of the early church, Christian theology has consistently recognized the concept of Christology. The topic of the divinity and humanity of Christ has attracted a wide range of attention among theologians. Despite this recognition, there have been some conflicts specifically related to Christological theology. The study rests on the nature and understanding of the divinity and the humanity of Christ. The present study will address the understanding of the theological concept of Christology and how we perceive the coexistence of human and divine aspects. Thus, exploring the human and the divine attributes of Jesus Christ in dialogue with contemporary experts. The Christological theology emphasizes the importance of Jesus Christ in Christian theological contemplation. Christology addresses the fundamental inquiry of "Who is Jesus" due to skeptics and limited believers. It also stresses the need for categorization of Christ's divine and human nature, similar to the disciples' question about Jesus' obedience to every circumstance.
Keywords: inclusive education; teacher training.; Quantitative analysis; Deafness; Social Design; Precarity; Graphics; Local Print Shops; human; nature; theology; Divine; Christ